2014
DOI: 10.1111/imj.12315
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐year trends in benzodiazepine dispensing in the Australian population

Abstract: Despite a modest overall decline in the amount of benzodiazepine dispensed, the level of use is still likely to reflect relative over-prescribing given the paucity of accepted indications for long-term use. Since 1998, there was a polynomial increase in quantity dispensed per script. The WHO-defined DDD for clonazepam seems inappropriate and could impede monitoring of its abuse. Other problems include lack of national data for medications not subsidised on PBS/Repatriation PBS. A broad policy approach is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 19 publications
7
60
2
6
Order By: Relevance
“…It is notable that such patterns of use aligns with Australian data showing alprazolam and diazepam to be among the most widely prescribed (Islam et al, 2014) and misused (Nielsen et al, 2008;Stafford & Burns, 2012) benzodiazepines, and also the most widely studied in relation to exploring the benzodiazepine-aggression link (Albrecht et al, 2014).…”
Section: Main Analysessupporting
confidence: 68%
“…It is notable that such patterns of use aligns with Australian data showing alprazolam and diazepam to be among the most widely prescribed (Islam et al, 2014) and misused (Nielsen et al, 2008;Stafford & Burns, 2012) benzodiazepines, and also the most widely studied in relation to exploring the benzodiazepine-aggression link (Albrecht et al, 2014).…”
Section: Main Analysessupporting
confidence: 68%
“…The PBS database captures all subsidized drug formulations, cost and amount of dispensing and period of drug dispensed by pharmacists for patients used at home [29]. Drug dispensed data on the PBS database were used in research studied and shown to represent trends of drug utilisation in Australia [30,31]. Rosiglitazone and pioglitazone are listed as subsidised drugs for all Australians therefore a complete record of dispensed medicines was obtained [3].…”
Section: Methodsmentioning
confidence: 99%
“…Alprazolam became the second most popular drug, increasing more than eightfold. 1 Of particular concern are the patients who have been using benzodiazepines for more than six months. There are few indications for long-term therapy and they are generally controversial.…”
Section: Introductionmentioning
confidence: 99%